Effect of Different Level of Phosphorus and Sulphur on Growth and Yield Attributes of Sesame - Kalegore, N. K.; Kirde, G. D.; Bhusari, S. A.; Kasle, S. V.; Shelke, R. I. (International Journal of Economic Plants, 2018)
A field experiment was conducted to study the effect of different level of phosphorus and sulphur on yield attributes and yield of sesame during kharif 2011–12 at Department of Agronomy, College of Agriculture, Latur. The soil of the experimental plot was clay texture, low in available nitrogen (186.8 kg ha-1), medium in available phosphorous (15.9 kg ha-1 ), high in available potassium (343.2 kg ha-1 ) and slightly alkaline (pH 8.02) in reaction. The experiment field was uniform and well levelled. Gross plot size was 5.4×4.2 m2 and net plot size was 4.5×3.6 m2 respectively. The experiment was laid out in Factorial Randomized Block Design with three replications. The spacing 675 cm2 and recommended dose of fertilizers (50:25:00 NKK ha-1) were used. The treatments consists of three levels each of phosphorus and sulphur. The phosphorus applied as 20 kg P205 ha-1, 25 kg P205 ha-1, 30 kg P205 ha-1 and 20 kg S ha-1, 25 kg S ha-1, 30 kg S ha-1. The application of 30 kg P2O5 was recorded significantly higher growth and yield attributing character over the rest of the phosphorus levels. Among three sulphurtreatment 30 kg sulphur ha-1 was recorded significantly higher growth and yield attributing characters over the application of 20 and 25 kg sulphur ha-1